Gametogenesis and Spawning of Solenastrea bournoni and Stephanocoenia intersepta in Southeast Florida, USA. (16th August 2012) - Lueg, Jenna R.; Moulding, Alison L.; Kosmynin, Vladimir N.; Gilliam, David S.
Abstract : This study constitutes the first report of the gametogenic cycle of the scleractinian corals Solenastrea bournoni and Stephanocoenia intersepta . Tissue samples were collected near Ft. Lauderdale, Florida, USA between July 2008 and November 2009 and processed for histological examination in an effort to determine reproductive mode and potential spawning times. Both S. bournoni and S. intersepta are gonochoric, broadcast spawning species. Gametogenesis of S. bournoni began in April or May while S. intersepta had a much longer oogenic cycle that began in December with spermatogenesis beginning in July. Though spawning was not observed in situ, spawning was inferred from the decrease of late stage gametes in histological samples. In addition, histological observations of oocyte resorption and released spermatozoa were used to corroborate spawning times. Data indicate that S. bournoni spawns in September while S. intersepta spawns after the full moon in late August or early September.